Fish Diversity in a Little-Known Border River Between China, North Korea, and Russia, According to Traditional and eDNA Surveys - Chen Tian; Zhixian Sun; Yutian Fang; Dong Sheng; Bo Li; Cunqi Liu; Yahui Zhao (Diversity)
The Tumen River, which delineates the border between China, North Korea, and Russia, is a vital river in Northeast Asia. Understanding its current fish diversity holds significant scientific value for aquatic ecological protection. Therefore, traditional and eDNA sampling were conducted from 2022 to 2023. Integrating the historical literature with our field collection results reveals that the Tumen River has a total of 64 native fish species, of which 51 species have been surveyed in the wild. The fish composition is mainly dominated by cold-water species, with a high proportion of these being rare, endangered, and nationally protected. eDNA surveys are crucial complements in boundary rivers where traditional methods are not feasible. The results indicated that α diversity values were highest in the Hunchunhe River, attributed to the favorable natural geographical conditions and effective conservation efforts. Recently, the fish diversity in the Tumen River has been disrupted, primarily reflected in the absence of migratory species such as Oncorhynchus gorbuscha and Pseudaspius hakonensis. The study suggests that establishing nature reserves, preventing and controlling alien species, and strengthening international cooperation are key to protect fish diversity.